PREDICTIVE INSTRUMENT FOR ASYMPTOMATIC EARLY-STAGE CHRONIC LYMPHOCYTIC LEUKEMIA PATIENTS-SINGLE CENTE EXPERIANCE - Trajkova, Sanja; Pivkova-Veljanovska, ALeksandra; Krstevska-Balkanov, Svetlana; Ridova, Nevenka; Stojanovska, Simona; Labacevski, Bojan; Panovska-Stavridis, Irina (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
Early-stage patients with Chronic  lymphocytic leukemia (CLL) are diagnosed without need for treatment, managed with following. The distinct course of the disease  is diverse, and  planing  treatment is barely projected at diagnosis. The aim of the study was first-time evaluation of  international prognostic score to predict time to first treatment (TFT) in patients with early stage CLL   (International Prognostic Score for Early-stage CLL IPS-E). Retrospective study of asymptomatic patients with CLL at early stage of disease in a period of time from January 2011 to January 2021. The median follow-up was 60 months (1-120 months). Individual patient data from 120 treatment-naÃ¯ve CLL patients with Binet A stage were analyzed to composed International Prognostic Score for Early-stage CLL and correlated with Time to treatment failure (TTF).  Using IPS-E patients were distributed in three groups: low risk with 7, 5%, intermediate risk with 44 % and high risk patients 49%. Average TFS was 29, 3 months for low risk group, 28, 6 months for intermediate-risk group and 27,1 months for high-risk group. Using  prognostic  nomogram we calculated 5 years probability of survival for low, intermediate and high risk group: 73%, 72% and 70% respectively with projected median survival of 9, 1 year for low risk group and 9, 0 year, 8, 9 years for intermediate and high risk groups. Keywords:   CLL, asymptomatic, early stage, IPS-E. https://doi.org/10.55302/JMS2143081t